2022
DOI: 10.1186/s12944-022-01739-2
|View full text |Cite
|
Sign up to set email alerts
|

BMI modifies HDL-C effects on coronary artery bypass grafting outcomes

Abstract: Background Despite the recognized implications of high-density lipoprotein cholesterol (HDL-C) in cardiovascular diseases, the role of body mass index (BMI) in HDL-C association with cardiovascular outcomes remains unclear. This study investigated the possible modifying implications of BMI on the correlation between HDL-C and coronary artery bypass grafting (CABG) outcomes. Methods The present cohort included isolated CABG patients (median follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A second explanation may be that patients with higher cholesterol concentrations are more likely to be taking medications such as β-blockers and angiotensin-converting enzyme inhibitors before their admission; as a result, these medications may individually or synergistically contribute to the paradoxically lower risk of patients with 70 mg/dl < LDL-C ≤ 100 mg/dl as compared to patients with LDL-C < 70 mg/dl. A third explanation may be that in patients with very low serum LDL-C levels, HDL-C levels are also comparatively lower, which may be prognostically more impactful than the former [ 32 ]. Accordingly, Ogita et al revealed that, despite achieving optimal LDL-C control after coronary revascularization, diabetic patients with low serum HDL-C levels had higher rates of major cardiovascular events [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A second explanation may be that patients with higher cholesterol concentrations are more likely to be taking medications such as β-blockers and angiotensin-converting enzyme inhibitors before their admission; as a result, these medications may individually or synergistically contribute to the paradoxically lower risk of patients with 70 mg/dl < LDL-C ≤ 100 mg/dl as compared to patients with LDL-C < 70 mg/dl. A third explanation may be that in patients with very low serum LDL-C levels, HDL-C levels are also comparatively lower, which may be prognostically more impactful than the former [ 32 ]. Accordingly, Ogita et al revealed that, despite achieving optimal LDL-C control after coronary revascularization, diabetic patients with low serum HDL-C levels had higher rates of major cardiovascular events [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…protective cardiovascular effects of HDL-cholesterol may be attenuated in individuals with higher BMI [39]. This raises an intriguing question concerning the potential modulation of statin efficacy in the context of elevated BMI.…”
Section: Plos Onementioning
confidence: 99%
“…Obesity is a complex, multifactorial, and largely preventable disease, affecting up to a third of the world's population in the recent decades. [1][2][3] Obesity is a major risk factor for cardiovascular complications and heart failure by predisposing to hypertension, dyslipidemia, diabetes mellitus, coronary artery disease, and sleep apnea syndrome. [4][5][6][7][8][9][10] Several mechanisms are involved in the pathogenesis of left ventricle (LV) dysfunction in obese individuals.…”
Section: Introductionmentioning
confidence: 99%